Unlawful Acts in Sales and Purchase Agreements and the Protection of Good-Faith Buyers - Zahra, Nabilla; Abdullah, Ali; Kesuma, Diani (Jurnal Ilmu Hukum Kyadiren, 2026)
Sales and Purchase Agreements (Perjanjian Pengikatan Jual Beli—PPJBs) frequently give rise to disputes when legal defects arise in the transfer of land rights, particularly where such defects prejudice buyers acting in good faith. The tension between legal certainty of land ownership and the protection of good-faith parties remains a legal problem that has yet to be fully resolved in judicial practice. This study examines the application of the doctrine of unlawful acts in PPJBs and evaluates the form and effectiveness of legal protection afforded to landowners and good-faith buyers. Employing a normative legal research method, the study adopts statutory, conceptual, and case-based approaches, with particular attention to judicial decisions concerning PPJB disputes. The findings demonstrate that unlawful acts in PPJBs predominantly originate from the bad faith of one of the contracting parties or third parties. At the same time, courts tend to provide proportional protection to good-faith buyers without disregarding the rights of the lawful owner. The study concludes that effective legal protection in PPJB disputes can only be achieved through a balanced application of the principles of good faith and legal certainty within the agrarian law framework.